1996
DOI: 10.1021/jf950489t
|View full text |Cite
|
Sign up to set email alerts
|

Condensed Tannins Are Only Partially Responsible for Variations in Nutrient Digestibilities of Sorghum Grain Cultivars

Abstract: Nitrogen-corrected true metabolizable energy (TME n ) and true amino acid digestibility values were determined, using cecectomized cockerels, for 20 sorghum [Sorghum bicolor (L.) Moench] cultivars that ranged in catechin equivalent (CE) percentages from 0 to 3.88. There were significant (P e 0.01) overall inverse relationships between CE content and (1) the individual digestibilities of lysine, methionine, threonine, isoleucine, leucine, valine, phenylalanine, histidine, and arginine; (2) the mean digestibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
0
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 23 publications
(34 reference statements)
7
38
0
3
Order By: Relevance
“…As a consequence, our contention is that the anti-nutritive properties of phenolic compounds are not the sole domain of CT and to some extent are shared by the balance of polyphenols and phenolic acids found in grain sorghum. Instructively, Elkin, et al [65] concluded that condensed tannin is only partially responsible for variations in the nutrient quality. Also, phenolic compounds and phytate appear to share several anti-nutritive properties [11].…”
Section: "Non-tannin" Polyphenolic Compounds and Phenolic Acidsmentioning
confidence: 99%
“…As a consequence, our contention is that the anti-nutritive properties of phenolic compounds are not the sole domain of CT and to some extent are shared by the balance of polyphenols and phenolic acids found in grain sorghum. Instructively, Elkin, et al [65] concluded that condensed tannin is only partially responsible for variations in the nutrient quality. Also, phenolic compounds and phytate appear to share several anti-nutritive properties [11].…”
Section: "Non-tannin" Polyphenolic Compounds and Phenolic Acidsmentioning
confidence: 99%
“…-E-mail: laurence.lamothe@toulouse.inra.fr Sorghum (Sorghum bicolor) had not been used in poultry feeding for many years because its grain contains tannins, which reduce its digestibility and thus the performance of birds (Elkin et al, 1996;Nyachoti et al, 1997). However, today, several sorghum varieties are tannin-free and could be used in bird feeding (Gualtieri and Rapaccini, 1990;Selle et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…It is also used with plant proteins [11,16]. But, porcine pepsin (composed mainly of pepsin A) is used whatever the species despite some studies have shown that pepsins from different species show different enzymatic properties [3,22,28].…”
mentioning
confidence: 99%